2015
DOI: 10.15835/buasvmcn-hort:10999
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cutting size on the rooting of Thuja occidentalis 'Columna'

Abstract: Rooting process plays a key role in the vegetative propagation of the ornamental coniferous, and insufficient rooting causes substantial losses in the propagation industry. Cuttings of Thuja occidentalis ‚Columna' planted in the greenhouse of Mihai Viteazul Nursery Garden from Turda were examined after selecting the cuttings in three size categories. Experimental design included three cutting lengths (10, 15 and 20 cm) and each were growing without rooting hormones. Cutting length is an important factor that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Root number decreased at the TOD (Figure 3c) cuttings propagated in July compared to May propagation period. Szász-Len et al (2015b) reported that 15 cm cuttings obtained the highest root number at Thuja occidentalis 'Columna'. Hormone treatments could also greatly increase the number of adventitious root formation (Panea and Blada, 2016).…”
Section: Figure 2 Effect Of Stem Cutting Length and Propagation Perio...mentioning
confidence: 99%
“…Root number decreased at the TOD (Figure 3c) cuttings propagated in July compared to May propagation period. Szász-Len et al (2015b) reported that 15 cm cuttings obtained the highest root number at Thuja occidentalis 'Columna'. Hormone treatments could also greatly increase the number of adventitious root formation (Panea and Blada, 2016).…”
Section: Figure 2 Effect Of Stem Cutting Length and Propagation Perio...mentioning
confidence: 99%